Clinical Outcome After Microsurgical Resection of Central Neurocytoma: A Single-Centre Analysis of 15 Years - Cao, Dan; Chen, Yong; Guo, Zhengqian; Ou, Yibo; Chen, Jian (Frontiers in Neurology, 2021)
Objective: This study aimed to explore the immediate postoperative and long-term outcomes of central neurocytoma (CN) based on 15 years of experience in our institution. Methods: This single-institution study collected data of 43 patients with CN who underwent surgery between 2005 and 2020. We reviewed data of clinical, immediate postoperative outcome, and long-term outcome of patients. More specifically, we divided complications into neurological and regional complications groups. Results: Among the 43 patients with CN who underwent surgery, the transcortical (72.1%) or transcallosal (25.6%) approach was used. There were 18 patients (41.9%) who complained about postoperative neurological complications, including motor weakness (25.6%), memory deficit (18.6%), aphasia (7.0%), and seizure (4.7%). In addition, 18 patients suffered postoperative regional complications such as hydrocephalus (2.3%), hematoma (34.9%), infection (4.7%), and subcutaneous hydrops (2.3%). Only one-quarter of patients had suffered permanent surgical complications. The majority of patients recovered from the deficit and could turn back to normal life. There were no significant differences in the clinical outcomes between transcortical and transcallosal approaches. At a median follow-up of 61.8 months, the 5-year overall survival and progression-free survival were 87.0 and 74.0%, respectively. A multivariate Cox model analysis showed that the extent of resection was not related to progression-free survival. However, the extent of resection was significantly associated with overall survival, and gross total resection decreased the risk of death. Conclusions: Patients with CN show favorable outcomes after surgery. The transcortical and transcallosal approaches have similar postoperative complication rates and long-term follow-up outcomes. In terms of long-term prognosis, maximal safety resection should be the first choice of CN.